Guaranty funds and risk-taking evidence from the insurance industry - Lee, Soon-Jae; Mayers, David; Smith, Clifford W. (Journal of Financial Economics, 1997)
This paper examines change in property-liability insurers' risk-taking around enactments of state guaranty fund laws. Our evidence suggests that the risk of insurers' asset portfolios increases following enactments. But this increase in risk is significant only for stock insurers. Our evidence of increased risk-taking following guaranty-fund adoptions suggests that the way these funds are organized creates counterproductive investment incentives, especially for stock companies. Because these laws were enacted by states over the period 1969–1981, our evidence on changes in risk-taking helps resolve statistical problems that have been troublesome for studies of bank deposit insurance.